2012
DOI: 10.5018/economics-ejournal.ja.2012-39
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Exchange Rate Pass-Through in the Euro Area: New Evidence from Smooth Transition Models

Abstract: This paper examines the presence of asymmetric behavior in exchange rate passthrough (ERPT) to CPI inflation in 12 euro area (EA) countries. Using a class of nonlinear smooth transition models, the author tests for asymmetry with respect to the direction and the magnitude of exchange rate changes. On the one hand, the author finds only 5 out of 12 EA countries showing asymmetric pass-through related to exchange rate appreciations and depreciations. Results are somewhat mixed with no clear evidence about the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 19 publications
(25 reference statements)
2
23
0
Order By: Relevance
“…The business‐cycle dependence of exchange rate pass‐through has been addressed in: (i) Goldfajn and Werlang (), who employ a linear panel for 71 countries in which they include a cyclical measure of output; which confirms that pass‐through effects are stronger during times of expansion than during weak growth periods; (ii) Ben Cheikh () who uses nonlinear smooth transition regression models to reveal a significant business cycle dependence for 6 of 12 euro area countries; (iii) Donayre and Panovska () who present a Bayesian threshold vector autoregressive model for Canada and Mexico, where the same nonlinear effect is found. An explicit reference to capacity constraint‐type theory cannot be found as of yet in such papers about state‐dependent exchange rate pass‐through, but the underlying rationale can sometimes be read ‘between the lines’.…”
Section: Empirical Analysismentioning
confidence: 99%
“…The business‐cycle dependence of exchange rate pass‐through has been addressed in: (i) Goldfajn and Werlang (), who employ a linear panel for 71 countries in which they include a cyclical measure of output; which confirms that pass‐through effects are stronger during times of expansion than during weak growth periods; (ii) Ben Cheikh () who uses nonlinear smooth transition regression models to reveal a significant business cycle dependence for 6 of 12 euro area countries; (iii) Donayre and Panovska () who present a Bayesian threshold vector autoregressive model for Canada and Mexico, where the same nonlinear effect is found. An explicit reference to capacity constraint‐type theory cannot be found as of yet in such papers about state‐dependent exchange rate pass‐through, but the underlying rationale can sometimes be read ‘between the lines’.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Several studies have shown that ERPT is stronger for large exchange rate changes, a kind of nonlinear response typically associated with menu costs (Pollard and Coughlin, 2004;Posedel and Tica, 2009;Przystupa and Wrobel, 2011;Ben Cheikh, 2012;Bussière, 2013). Macroeconomic risk has also been identified as a factor influencing ERPT.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, countries with higher inflation rates tend also to have a higher degree of exchange‐rate pass‐through to prices. Ben Cheikh () and Ben Cheikh and Rault () explore the Taylor hypothesis in euro area countries and find mixed results, depending on the sample size…”
Section: Introductionmentioning
confidence: 99%
“…This technique allows the regression coefficients to change gradually, with the shape of a logistic function, when moving from one regime to another. See Ben Cheikh () and Nogueira and Len‐Ledesma () for an application of this model to time series of individual countries. We consider this an interesting avenue for future research.…”
mentioning
confidence: 99%